Endothelial function in highly endurance-trained men: Effects of acute exercise - Rognmo, O.; Bjornstad, T. H.; Kahrs, C.; Tjonna, A. E.; Bye, A.; Haram, P. M; Stolen, T.; Slordahl, S.; Wisloff, U. (The Journal of Strength and Conditioning Research, 2008)
Exercise training reverses endothelial dysfunction, but the effect in young, healthy subjects is less clear. We determined the influence of maximal oxygen uptake (VO2max) and a single bout of high-intensity exercise on flow-mediated dilatation (FMD), brachial artery diameter, peak blood flow, nitric oxide (NO) bioavailability, and antioxidant status in highly endurance-trained men and their sedentary counterparts. Ten men athletes (mean ± SEM age 23.5 ± 0.9 years, height 182.6 ± 2.4 cm, weight 72.5 ± 2.4 kg, VO2max 75.9 ± 0.8 mL/kg·min) and seven healthy controls (age 25.4 ± 1.2 years, height 183.9 ± 3.74 cm, weight 92.8 ± 3.9 kg, VO2max 47.7 ± 1.7 mL/kg·min) took part in the study. FMD, brachial artery diameter, and peak blood flow were measured using echo-Doppler before, 1 hour, 24 hours, and 48 hours after a single bout of interval running for 5 × 5 minutes at 90% of maximal heart rate. NO bioavailability and antioxidant status in blood were measured at all time points. Maximal arterial diameter and peak flow were 10-15% (P < 0.02) and 28-35% (P < 0.02) larger, respectively, in athletes vs. controls at all time points, and similar FMD were observed, apart from a transient decay of FMD in athletes 1 hour post exercise. NO bioavailability increased significantly after exercise in both groups and decreased to baseline levels after 24 hours in controls but remained increased 80% and 93% above baseline 24 and 48 hours post exercise in athletes. Antioxidant status was equal in the two groups at baseline and increased by approximately 10% 1 hour post exercise, an effect that lasted for 24 hours. Athletes had larger arterial diameter but similar FMD as untrained subjects, i.e., athletes had larger capacity for blood transport compared with their untrained counterparts. The observed FMD, bioavailability of NO, and antioxidant status in blood were highly dependent on the time elapsed after the exercise session.